2014
DOI: 10.1186/s40172-014-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

The levelling effect of product market competition on gender wage discrimination

Abstract: Using linked employer-employee panel data for West Germany that include direct information on the competition faced by plants, we investigate the effect of product market competition on the gender pay gap. Controlling for match fixed effects, we find that intensified competition significantly lowers the unexplained gap in plants with neither collective agreements nor a works council. Conversely, there is no effect in plants with these types of worker codetermination, which are unlikely to have enough discretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…To our knowledge, the influence of competition on the wage gap between gay and straight men has not been considered, but several papers have considered how competition influences the gender wage gap using the predictions of Becker (1957)'s model. Using various datasets, studies have found evidence of a shrinking gender wage gap consistent with model predictions in West Germany (Hirsch et al 2014), Sweden (Heyman et al 2013), Hungary (Jolliffe and Campos 2005), Austria (Weber and Zulehner 2014), Japan (Kawaguchi 2007), as well as crosscountry studies (Weichselbaumer and Winter-Ebmer 2007;Zweimuller et al 2008). Within the United States, Black and Brainerd (2004) analyze the influence of competition from trade and the gender wage gap across industries and find evidence that increasing trade reduces the ability of firms to discriminate against women.…”
Section: Literature Reviewmentioning
confidence: 69%
See 1 more Smart Citation
“…To our knowledge, the influence of competition on the wage gap between gay and straight men has not been considered, but several papers have considered how competition influences the gender wage gap using the predictions of Becker (1957)'s model. Using various datasets, studies have found evidence of a shrinking gender wage gap consistent with model predictions in West Germany (Hirsch et al 2014), Sweden (Heyman et al 2013), Hungary (Jolliffe and Campos 2005), Austria (Weber and Zulehner 2014), Japan (Kawaguchi 2007), as well as crosscountry studies (Weichselbaumer and Winter-Ebmer 2007;Zweimuller et al 2008). Within the United States, Black and Brainerd (2004) analyze the influence of competition from trade and the gender wage gap across industries and find evidence that increasing trade reduces the ability of firms to discriminate against women.…”
Section: Literature Reviewmentioning
confidence: 69%
“…Many of the previous findings rely on data from individual sectors. However, Hirsch et al () note that there may be a large variance of market competition within the sector. An alternative measure of market competitiveness, one employed in Hoover (), Hoover et al (), and Zweimuller et al (), is the North American Economic Freedom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More specifically, we add interaction terms between the years after return and a younger or older returnee dummy variable when estimating wage premium dynamics on samples of individuals aged 15-35 and more than 36 years, respectively. A similar approach was applied by Hirsch, Oberfichtner, and Schnabel, 2014 to analyse wage assimilation among ethnic German immigrants to Germany. The functional form of returnee wage premium regression is the following:…”
Section: Empirical Strategymentioning
confidence: 99%
“…For example,Black and Strahan (2001) show that removing regulations on the banking sector in US led to a reduction in the gender wage gap in this industry whileHirsch et al (2014) find that the gender wage gap is smaller at firms in Germany that face more product market competition.13 This intuition is formalized in Biddle and Hamermesh (2013) which develops an equilibrium search model that shows that employers discriminate less in a tight labour market and is tested in recent work byBaert et al (2015), who find that interview rates for immigrants in a correspondence study in Belgium are higher in occupations for which vacancies are difficult to fill.…”
mentioning
confidence: 99%